Prognostic tools for hypertrophic scar formation based on fundamental differences in systemic immunity. Issue 1 (17th August 2020) - de Bakker, Erik; van der Putten, Mirthe A. M.; Heymans, Martijn W.; Spiekstra, Sander W.; Waaijman, Taco; Butzelaar, Liselotte; Negenborn, Vera L.; Beekman, Vivian K.; Akpinar, Erman O.; Rustemeyer, Thomas; Niessen, Frank B.; Gibbs, Susan
Abstract: Unpredictable hypertrophic scarring (HS) occurs after approximately 35% of all surgical procedures and causes significant physical and psychological complaints. Parallel to the need to understanding the mechanisms underlying HS formation, a prognostic tool is needed. The objective was to determine whether (systemic) immunological differences exist between patients who develop HS and those who develop normotrophic scars (NS) and to assess whether those differences can be used to identify patients prone to developing HS. A prospective cohort study with NS and HS groups in which (a) cytokine release by peripheral blood mononuclear cells (PBMC) and (b) the irritation threshold (IT) after an irritant (sodium lauryl sulphate) patch test was evaluated. Univariate regression analysis of PBMC cytokine secretion showed that low MCP‐1, IL‐8, IL‐18 and IL‐23 levels have a strong correlation with HS ( P  < .010‐0.004; AUC = 0.790‐0.883). Notably, combinations of two or three cytokines (TNF‐a, MCP‐1 and IL‐23; AUC: 0.942, Nagelkerke R 2 : 0.727) showed an improved AUC indicating a better correlation with HS than single cytokine analysis. These combination models produce good prognostic results over a broad probability range (sensitivity: 93.8%, specificity 86.7%, accuracy 90, 25% between probability 0.3 and 0.7). Furthermore, the HS group had a lower IT than the NS group and an accuracy of 68%. In conclusion, very fundamental immunological differences exist between individuals who develop HS and those who do not, whereas the cytokine assay forms the basis of a predictive prognostic test for HS formation, the less invasive, easily performed irritant skin patch test is more accessible for daily practice.